Implementation of the MOORA method in the scholarship determination decision support system at (fundus desenvolvimentu capital humana) - Ivéria Correia Fátima Marques; Jaime da Costa Lobo Soares (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
Equitable access to education remains a significant challenge, particularly in the distribution of scholarship funds, which often lacks transparency and efficiency due to manual selection processes. In Timor-Leste, the Human Capital Development Fund (FDCH) plays a vital role in supporting human resource development; however, its scholarship selection system is still prone to errors and subjectivity. This study aims to develop a more objective and efficient scholarship selection system. The method used in this research is a Decision Support System (DSS) based on the Multi-Objective Optimization on the Basis of Ratio (MOORA) method, which evaluates multiple criteria such as academic performance, economic background, and other relevant factors. The system is designed to process data systematically and generate ranking results for scholarship candidates. The results show that the implementation of the MOORA method can improve the accuracy, consistency, and transparency of the selection process compared to conventional methods. The system is able to rank candidates objectively based on predefined criteria. In conclusion, the proposed DSS using the MOORA method provides an effective solution for improving the fairness and efficiency of scholarship selection, and can support better decision-making in educational institutions